Harnessing the Blue Economy: Ethnobotanical Insights into Mangrove-Derived Functional Foods for Climate-Resilient Futures - Syari Mela Simanjuntak; Duryat; Melya Riniarti (Forest and Nature, 2025)
Climate change threatens food security at the local, regional, and global levels. Optimizing the potential of the blue ecosystem, especially mangrove forest products, can contribute to overcoming the food crisis. This study aims to document the ethnobotanical practices related to the utilization of mangroves as a food source in the South Lampung Regency.  This study employed the snowball sampling method, utilizing open-ended interviews with respondents. The collected data, including species types, utilized plant parts, processed products, and associated properties, were analyzed using descriptive-analytical methods to identify patterns, relationships, and factors influencing the practice of mangrove-based food utilization. The results reveal that the people of South Lampung Regency utilize four mangrove species as ethnobotanical food sources. These include the fruit (excluding the root) of Rhizophora mucronata, which is processed into coffee; the young leaves of Avicennia marina, consumed as fresh vegetables; its sap, which is processed into health beverages; and its fruit, which is used to produce flour for cake-making. Additionally, Acanthus ilicifolius is processed into tea and rempeyek, a traditional cracker made from leaf fragments. Beyond their nutritional value, mangroves possess bioactive properties, including antifertility, antioxidant, analgesic, anticholesterol, antihypertensive, antitussive, and anti-inflammatory effects, highlighting their potential for development into functional foods. Such diversification could address various social and economic challenges in South Lampung Regency. However, limitations in human resource capacity hinder the optimization of mangrove utilization, resulting in a lack of diversity and innovation in the selection of species, utilized plant parts, processed products, and processing techniques.